Exploring Children's Peer Relationships through Verbal and Non-verbal Communication: A Qualitative Action Research Focused on Waldorf Pedagogy - Aida Milena Montenegro Mantilla (Asociación Colombiana de Profesores de Ingles, 2007)
This study analyzes the relationships that children around seven and eight years old establish in a classroom. It shows that peer relationships have a positive dimension with features such as the development of children's creativity to communicate and modify norms. These features were found through an analysis of children's verbal and non-verbal communication and an interdisciplinary view of children's learning process from Rudolf Steiner, founder of Waldorf Pedagogy, and Jean Piaget and Lev Vygotsky, specialists in children's cognitive and social dimensions. This research is an invitation to recognize children's capacity to construct their own rules in peer relationships.